Food court ordering system using mobile application (fooCOSUMA) - Engku Muhammad Syuhada, Raja Omar (2012)
Food court ordering system is the way to manage a flow or process in the food court and mobile application device has been use to complete the process in managing food court. The project was to design and develop a food court ordering system using mobile application that will potentially used in the biggest restaurant such as food court,to increase the performance and quality of the services.The project has been focused on the food ordering process at the food court.This project is based on the System Development Life Cycle (SDLC) to achieve the entire objectives in a given period of time. System Development Life Cycle (SDLC) is focuses on the interaction of planning,analysis,and design which leads to implementation followed by testing and evaluation.This food court ordering system was design to allow waiters to takes customer orders at the food court through mobile device.The mobile device is connecting to the server through wireless connection.This system also designed for food court manager to manage their menu and order that has been send by food court waiters.They were allowed to add,update or remove items from food court menu.Besides that,this system is designed to calculate customer billing automatically and make the food court system more systematic.